Exploring the effect of workplace spirituality on job embeddedness among higher secondary school teachers in Ernakulam district - Smitha Rajappan; Rohini S. Nair; Kirupa Priyadarshini M.; V. Sivakumar (Cogent Business & Management, 2017)
The quality of education is determined by the quality of the teachers. As teachers are entrusted with the responsibility of shaping and guiding the future citizens of a nation, it is essential for them to be involved and committed toward their job. This brings out the importance of retaining teachers in their job. The concept of workplace spirituality (WPS) brings in the very feeling of being connected to the workplace, which, undoubtedly helps them to remain attached to the job. The study tries to understand the relationship between WPS and job embeddedness (JE) among the higher secondary school teachers in Ernakulam District. WPS was measured using the scale adapted from Milliman et al. and JE was measured using the scale developed by Mitchell et al. A sample size of 105 was selected using simple random sampling method. The study found a satisfactorily good level of WPS and JE among the respondents. The result of the study also shows a significant positive relationship between WPS and JE.
Keywords: 650